Planning for succession in family businesses - Sonfield, Matthew C. (2015)
This article compares a sample of US family businesses with a sample of Arab/Islamic family businesses from Egypt, Kuwait and Lebanon, with regard to the degree to which top management has formulated specific plans for the future succession of junior family members into top management positions (total N = 485). ANCOVA analysis indicates that the Arab/Islamic family businesses' top managers engage in the formulation of such succession plans to a statistically significant greater degree than do the US managers. The two dissimilar cultural contexts are examined, which offer reasons for this research finding, and implications are presented for future research.